Synchronisation of oestrus of goats treated with progestagen-impregnated intravaginal sponges and PMSG, and reproductive performance following natural mating or A.I. with frozen semen - Bongso, T.A.; I., Fatimah; Dass, S. (Elsevier, 1982)
Oestrus was synchronised in 88 goats using progestagen-impregnated intravaginal sponges (60 mg Repromap; Upjohn) left in place for 17 days, followed by intramuscular injection of PMSG (300 i.u.) at sponge withdrawal. The percentages of does that came into oestrus in 0–24, 25–48, 49–72 and 73–96 h periods were 42, 30.5, 10.5 and 6.5 (cumulative 89.5%). The time of onset of oestrus ranged from 16 to 40 h. Breeding at the synchronised oestrus using intact bucks (24–96 h) or artificial insemination with frozen-thawed semen, at fixed times of 24, 48, 72 and 96 h, resulted in 71% and 81% conceptions respectively. Intrauterine deposition of semen was possible in 31.3%, 62.5%, 87.5% and 6.3% of cases at 24, 48, 72 and 96 h respectively. Twinning percentages were 54.5% and 56% for natural mating and artificial insemination. Kidding was spread over a 14-day period with mean gestation lengths of 149 days for singletons and 147 days for twins. The results indicate that use of progestagen-impregnated sponges with PMSG is an efficient method of synchronisation of oestrus and may result in increased fertility in goats and, if used with A.I. with frozen semen, may contribute to increased breeding efficiency and rate of genetic improvement of goats in Asia.